Downy User Loyalty: The Influence of Brand Attractiveness, Experience, Trust, and Satisfaction - Rahmawati, Auliyya Ayu; Setyawan, Anton Agus (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study analyzes the influence of brand attractiveness, brand experience, brand trust, and brand satisfaction on brand loyalty toward Downy fabric softener goods sold in Indonesia. Methodology/approach: This investigation employed a numerical methodology, delivering surveys to 150 Downy users 17 years of age or older, who had experience with the product for at least three months. Purposive sampling was applied, and the data were examined using SPSS, employing validity and reliability assessments alongside multiple linear regression analysis. Results: The results suggest that brand attractiveness, experience, and satisfaction positively and significantly affect brand loyalty. Brand satisfaction is the most influential factor, even though faith in the brand does not notably shape loyalty. These findings highlight that consumer loyalty is more strongly driven by satisfaction and direct product experience than by trust. Conclusions: The study concludes that in the fabric care industry, customer loyalty is primarily formed through positive experience and high satisfaction. Theoretically, these findings position brand trust as a supporting factor rather than a direct driver of loyalty. Limitations: This study is limited to one brand and selected variables; it is advisable that subsequent investigations broaden their focus to include different brands and additional determinants. Contributions: This study offers empirical insights into the key determinants of brand loyalty in the fabric care industry, emphasizing the dominant role of brand satisfaction compared to other brand-related factors.